Pediatric multiple sclerosis: a review - Alroughani, Raed; Boyko, Alexey (BMC neurology, 2018)
Background Pediatric-onset multiple sclerosis (POMS) prevalence and incidence rates are increasing globally. No disease-modifying therapy are approved for MS pediatric population. Hence, we aim to review the literature on POMS to guide treating physicians on the current understanding of diagnosis and management of pediatric MS. Methods The authors performed a literature search and reviewed the current understanding on risk factors and disease parameters in order to discuss the challenges in assessing and implementing diagnosis and therapy in clinical practice. Results The revised International Pediatric MS group diagnostic criteria improved the accuracy of diagnosis. Identification of red flags and mimickers (e.g. acute disseminated encephalomyelitis and neuromyelitis optica) are vital before establishing a definitive diagnosis. Possible etiology and mechanisms including both environmental and genetic risk factors are highlighted. Pediatric MS patients tend to have active inflammatory disease course with a tendency to have brainstem / cerebellar presentations at onset. Due to efficient repair mechanisms at early life, pediatric MS patients tend to have longer time to reach EDSS 6 but reach it at earlier age. Although no therapeutic randomized clinical trials were conducted in pediatric cohorts, open-label multi-center studies reported efficacy and safety results with beta interferons, glatiramer acetate and natalizumab in similar adult cohorts. Several randomized clinical trials assessing the efficacy and safety of oral disease-modifying therapies are ongoing in pediatric MS patients. Conclusion Pediatric MS has been increasingly recognized to have a more inflammatory course with frequent infratentorial presentations at onset, which would have important implications in the future management of pediatric cohorts while awaiting the results of ongoing clinical trials.